Chitosan-based melatonin bilayer coating for maintaining quality of fresh-cut products. (1st May 2020) - Zhao, Hangyue; Wang, Lei; Belwal, Tarun; Jiang, Yunhong; Li, Dong; Xu, Yanqun; Luo, Zisheng; Li, Li
Graphical abstract: Highlights: This is the first comprehensive study incorporating melatonin in chitosan films. The chitosan-based melatonin layer-by-layer assembly (CMLLA) was developed. Structural characterization verified the improved properties of CMLLA. The antioxidant and antimicrobial activities of CMLLA were improved. The CMLLA has great potential to positively maintain fruit post-harvested quality. Abstract: This work was designed to develop the chitosan-based melatonin layer-by-layer assembly (CMLLA) via the inclusion method. The structural characterizations and interaction present in CMLLA were investigated by the scanning electron microscope (SEM), X-ray diffraction (XRD) and Fourier Transform-Infrared spectroscopy (FTIR). The ratio of chitosan (CH) to carboxymethylcellulose (CMC) greatly influenced the mechanical properties, including the tensile strength, moisture content and color performance. Results showed that both antioxidant and antimicrobial properties of CMLLA were enhanced with the addition of melatonin (MLT). Furthermore, it was demonstrated that the CMLLA with 1.2 % (w/v) CH, 0.8 % (w/v) CMC and 50 mg/L MLT better contributed to the delay of chlorophyll degradation and the maintenance of shelf-life quality. Results from this study might open up new insights into the approaches of quality improvement of postharvest fresh products by incorporating the natural antioxidant compounds into natural polymers.